(untitled) (International Journal of Engineering and Computer Science, 2019)
This seminar paper deals with biometric authentication, using human facial geometry as the login verification parameter. Biometric is the measurement and statistical analysis of human’s unique physical and behavioral characteristics by mapping face geometry, fingerprints, iris, and voice. The aim of this seminar paper is to develop a functional Biometric Authentication System Using Face Geometry as the authentication method. Facial Geometry Authentication is a category of biometric technology that maps an individual’s facial features mathematically and stores the data as face-prints in a database. Meanwhile the objective of this paper is to improve data access security, enhance identification accuracy, and contribute to the improvement of the existing facial recognition systems, focusing mainly on increasing its accuracy performance. On the other hand, hacking into users’ privacy, loss of confidential information, and high running costs, among others geared the motivation to develop a biometric authentication system using face geometry. Furthermore, the software engineering methodology adopted in this seminar paper is the Structural System Analysis and Design Methodology (SSADM). The software is developed in Visual C-sharp, and the database in SQL Server 2012; using Microsoft Visual Studio 2012 as the integrated development environment. Besides, OpenCV 2.4.8 library is used for image processing, image mapping, and computer vision. The expected result of this seminar paper include: improved user data security, and increased efficiency in facial detection/recognition.